"Two Sides of the Same Coin": Benefits of Science-Art Collaboration and Field Immersion for Undergraduate Research Experiences - Susannah Sandrin; Becky Ball; Ishanshika Arora (MDPI AG, 2024)
This study examined how incorporating art into an upper-level undergraduate field-based ecology research course influenced students' communication and collaboration skills, their career goals, and how they conceptualized the scientific method. Student pairs designed an independent research study that used artwork and a scientific research poster to disseminate their findings at an end-of-term exhibit. Students enrolled in either a local or a (subsidized) travel abroad section of the course. Students in both sections found new or deeper connections between art and science, developed a more sophisticated understanding of the science method, became more confident with their science skills, and reported an expanded perspective on their future careers (often including field work and a wider geographic job search). Science-art student teams indicated they wanted more opportunities for collaborative work in the future, and that their final products were more professional due to their collaborations, as compared to science-science teams. Additionally, the travel abroad students benefitted from experiencing new ecosystems and cultures, from working with science and art professionals from other countries, and from working in an isolated field station without distractions.